Time-varying instrumental variable estimation - Liudas Giraitis; George Kapetanios; Massimiliano Marcellino (Queen Mary University of London, School of Economics and Finance, 2020)
We develop non-parametric instrumental variable estimation and inferential theory for econometric models with possibly endogenous regressors whose coefficients can vary over time either deterministically or stochastically, and the time-varying and uniform versions of the standard Hausman exogeneity test. After deriving the asymptotic properties of the proposed procedures, we assess their finite sample performance by means of a set of Monte Carlo experiments, and illustrate their application by means of an empirical example on the Phillips curve.
Keywords: C14; C26; C51; 330; Instrumental variables; Time-varying parameters; endogeneity; Hausman test; Non-parametric methods; Phillips curve